ABCG2 rs2231142 variant in hyperuricemia is modified by SLC2A9 and SLC22A12 polymorphisms and cardiovascular risk factors in an elderly community-dwelling population - Jia Liu; Wei Yang; Yun Li; Zhanyun Wei; Xiaojuan Dan (BMC, 2020)
Abstract Background The ABCG2 rs2231142 single nucleotide polymorphism (SNP) is one of the most significant genetic variants associated with hyperuricemia (HUA) in Asian populations. However, the risk of ABCG2 rs2231142 variants for HUA could interact with other important HUA risk variants and cardiovascular factors. This study investigated the effects of the combined association among ABCG2 rs2231142 and multiple HUA genetic variants or cardiovascular risk factors on HUA risk and serum uric acid (sUA) levels in an elderly Chinese population. Methods A total of 1206 participants over 65 years old were enrolled in this study. Physical and laboratory examinations were performed for all participants. The ABCG2 rs2231142, SLC2A9 rs3733591, and SLC22A12 rs893006 SNPs were assayed using a standardized protocol. Logistic regression analysis and liner regression were adjusted respectively to account for the association between ABCG2 rs2231142 and other genetic variants, as well as between cardiovascular risk factors and HUA risk and sUA levels. Results The prevalence of HUA was 14.71% in the elderly community-dwelling population. The ABCG2 rs2231142 risk T allele was associated with HUA risk (odds ratio (OR) = 1.63, 95% confidence interval (CI): 1.27-2.11; p = 1.65 × 10− 4) and with increased sUA levels (Beta = 0.16, p = 6.75 × 10− 9) in the whole study population. Linear regression analysis showed that the mean sUA level increased linearly with the number of risk alleles of the three candidate genetic variants (Beta = 0.18, p = 1.94 × 10− 12) The joint effect of the ABCG2 rs2231142 T allele and cardiovascular risk factors (obesity, hypertension and dyslipidemia) was also associated with increased HUA risk and sUA levels. Each copy of the risk T allele was significantly associated with enhanced HUA risk in patients with hypertriglyceridemia (OR = 2.52, 95% CI: 1.33-4.60; p = 0.003) compared to controls. Conclusion Our findings reinforce the importance of the ABCG2 rs2231143 variant as a crucial genetic locus for HUA in Chinese populations and demonstrated the combined effects of multiple genetic risk variants and cardiovascular risk exposures on HUA risk and increased sUA level.